Understanding the High Creep Resistance of MRI 230D Magnesium Alloy through Nanoindentation and Atom Probe Tomography - Dorothea Matschkal-Amberger (MDPI AG, 2021)
Due to their low density, magnesium alloys are very appealing for light-weight constructions. However, the use of the most common magnesium alloy, AZ91 (Mg 9 wt.% Al, 1 wt.% Zn), is limited to temperatures below 150 °C due to creep failure. Several alloys with an improved creep resistance have been developed in the past, for example the alloy MRI 230D or Ca-alloyed AZ91 variants. However, there is an ongoing discussion in the literature regarding the mechanisms of the improved creep resistance. One factor claimed to be responsible for the improved creep resistance is the intermetallic phases which form during casting. Another possible explanation is an increased creep resistance due to the formation of precipitates. To gain more insight into the improved creep resistance of MRI 230D, nanoindentation measurements have been performed on the different phases of as-cast, creep-deformed and heat-treated samples of MRI 230D and Ca-alloyed AZ91 variants. These nanoindentation measurements clearly show that the intermetallic phase (IP) of the alloy MRI 230D does not lose strength during creep deformation in contrast to the Ca-alloyed AZ91 variants. High-temperature nanoindentation measurements performed at 200 °C clearly show that the intermetallic phases of the MRI 230D alloy maintain their strength. This is in clear contrast to the Ca-alloyed AZ91 variants, where the IP is significantly softer at 200 °C than at room temperature. Atom probe measurements have been used to gain insight into the differences in terms of chemical composition between the IPs of MRI 230D and the Ca-alloyed AZ91 variants in order to understand the dissimilar behaviour in terms of strength loss with increasing temperature.